2006
DOI: 10.1080/15287390500246431
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ellagic Acid and Vitamin E Succinate on Antioxidant Enzymes Activities and Glutathione Levels in Different Brain Regions of Rats After Subchronic Exposure to TCDD

Abstract: Ellagic acid (EA) and vitamin E succinate (VES) were previously shown to protect against 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD)-induced reactive oxygen species (ROS) overproduction in certain brain regions of rats after subchronic exposure. The current study was designed to assess the modulation of antioxidant enzyme activities and glutathione (GSH) levels as protective measures for VES and EA against TCDD-induced ROS overproduction in four regions of rat brain. TCDD was administered to groups of rats a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 49 publications
6
26
0
Order By: Relevance
“…The results of this study are concomitant with the results of the study carried out by the [2] which showed that hypoglycemia may cause an increase in oxidative stress in the brain tissue, and also with the study carried out by [8] which stated that hypoglycemia has led to an increase in the level of MDA with the decreased activity of SOD and GSH content of the brain's cortex and is also consistent with studies conducted by [32], [33], [34] and [35]. The accumulation of large quantities of zinc in neurons as a well as the result of decreased glucose level; has led to an increase in the production of ROS in the nerve cells which led to increased oxidative stress in the brain cortex and the hypothalamus and hypoglycemic coma and brain injury are complications.…”
Section: Resultssupporting
confidence: 80%
“…The results of this study are concomitant with the results of the study carried out by the [2] which showed that hypoglycemia may cause an increase in oxidative stress in the brain tissue, and also with the study carried out by [8] which stated that hypoglycemia has led to an increase in the level of MDA with the decreased activity of SOD and GSH content of the brain's cortex and is also consistent with studies conducted by [32], [33], [34] and [35]. The accumulation of large quantities of zinc in neurons as a well as the result of decreased glucose level; has led to an increase in the production of ROS in the nerve cells which led to increased oxidative stress in the brain cortex and the hypothalamus and hypoglycemic coma and brain injury are complications.…”
Section: Resultssupporting
confidence: 80%
“…With respect to numerous reports in antioxidant role of EA on neuodegeneration [47][48][49][50], we can confirm anti-oxidative profile of EA. The SOD enzyme produces substrate for GPx activity in the brain under stressful situations [51,52].…”
Section: Discussionsupporting
confidence: 59%
“…However, the long-time study in reperfusion phase to show more specific role and perceive mechanism of EA effect should be designed in future studies. Several line of evidences consistently supports the claim that ellagic acid improves antioxidant enzymes and subsequently these enzymes might defend neuronal cells against produced free radicals in brain injuries [47,48,49]. Herein, we detected the two antioxidant enzymes (SOD and GPx) in the present or absence of ellagic acid in ischemic rats' tissues.…”
Section: Discussionsupporting
confidence: 50%
“…Four hydroxyl groups are attached to the ring system of the compound and may play a role in complex formation with free radicals [20]. EA was found to provide protection against many conditions associated with free radical formation including hemorrhage in rodents, skin tumorigenicity in mice, Aflatoxin B1-induced mutagenicity in rats, 2,3,7,8-tertrachlorodibenzo-p-dioxin (TCDD)-induced oxidative stress in rats, and TCDD-induced developmental toxicity in mice [20][21][22][23][24]. This study tested the possible protection by EA of both DCAinduced production of developmental toxic effects and DCA-induced production of ROS in zebrafish embryos.…”
Section: Introductionmentioning
confidence: 99%